EFEKTIVITAS DAKWAH MUSLIMAT NU DI DESA NYAMUK KECAMATAN KARIMUNJAWA KABUPATEN JEPARA - Ulfiana Ulfiana (Fakultas Dakwah dan Komunikasi Program Studi Komunikasi dan Penyiaran Islam, 2016)
This study aims to determine the method, implementation and influence of da'wah of Muslimat NU in Nyamuk Karimunjawa Jepara. This type of research is field research with qualitative approach. The subjects in the study were NU Muslimate chiefs, and members of NU Muslimat. Technique of collecting data using interview, observation, and documentation, while data analysis using qualitative analysis. The results of this study indicate that 1) Method of da'wah of Muslimat NU in Nyamuk, Karimunjawa, Jepara Regency is quite good, because da'wah method is done through organization activity. In the activities of da'wah is done through activities in Mosque and Mosque in some Moslem Village and hold public recitation every year at harah Muslimat NU; 2) Implementation of da'wah of Muslimat NU in Nyamuk, Karimunjawa, Jepara District include: delivering ukhuwah Islamiyah material to all members of Muslimat NU, giving understanding and freedom to NU members to associate with anyone without any negative assumptions to organizations other than Muslimat or NU, establishing cooperation and coordination with other women's Islamic organizations in religious and social events, providing compensation to those in need, conducting muslimat recitation activities in mosques and mosques; 3) The influence of da'wah Muslimat NU in Nyamuk, Karimunjawa, Jepara Regency include: can foster women about religious and social, giving knowledge and understanding about Islamic teachings to members of jama'ah, there are educational institutions that kindergarten and TPQ, Who participated in the development of Nyamuk Village, there are many mosque-learning activities in Musholla or Mosque in Nyamuk Village.